(untitled) (Journal of actual problems of jurisprudence, 2019)
This work gives some inaccuracies and drawbacks existing in “Sanitary-epidemiological rules and manufacturing entity designing standards, №3792 and in Ecological cords of laws of Republic of Kazakhstan. Recommendations of their elimination were given. This will let eliminate double interpretation of particular particles and build the corruption barrier.